Electronic properties of several two dimensional halides from ab initio calculations - Barhoumi, Mohamed; Abboud, Ali; Debbichi, Lamjed; Said, Moncef; Björkman, Torbjörn; Rocca, Dario; Lebègue, Sébastien (Beilstein Journal of Nanotechnology, 2019)
Using density functional theory, we study the electronic properties of several halide monolayers. We show that their electronic bandgaps, as obtained with the HSE hybrid functional, range between 3.0 and 7.5 eV and that their phonon spectra are dynamically stable. Additionally, we show that under an external electric field some of these systems exhibit a semiconductor-to-metal transition.
Keywords: density functional theory; electronic properties; halide monolayers